Associations between maternal stressful life events and child health outcomes in indigenous and non-indigenous groups in New Zealand - Paine S-J; Walker R; Lee A; Loring B; Signal TL (Taylor and Francis Group, 2023)
Exposure to stressful life events (SLE) around the time of pregnancy is associated with adverse health outcomes for mothers and children. Previous New Zealand research found Indigenous Māori women are more likely to be exposed to SLE than non-Māori, and are exposed to a higher number of SLE. The consequences of this for ethnic inequities in child health outcomes are unknown. This paper examines the relationship between patterns of maternal SLE exposure with child health and development outcomes at age 3 years, for Indigenous and non-Indigenous children. We found most children had a stressful early life environment at least sometimes, but more than a quarter of Māori children had a mother experiencing multiple SLE on all occasions measured. We found a clear association between maternal experiences of SLE and disordered child sleep and development concerns. While not able to fully assess the contribution of maternal SLE to ethnic inequities in child health outcomes, we did clearly demonstrate that more Māori children have mothers exposed to multiple SLE, and that these maternal SLE are associated with poorer child outcomes. The impacts of chronic SLE exposure need to be better understood, especially given the large ethnic disparity in chronic SLE exposure.
Keywords: Indigenous; maternal stress; stressful life events; childhealth; women’s health; inequities